Baitul Mal wat Tamwil (BMT): The Pillar of Islamic Microfinance in Indonesia - Bayani, Ahmad; Robby, Robby; Sobri, Ahmad (Master of Sharia Economics Program, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2025)
Baitul Mal wat Tamwil (BMT) is a sharia-based microfinance institution founded on both profit-oriented and social principles. Its functions include collecting funds from the community in the form of savings and deposits, administering these funds, and redistributing them through financing, receivables, or loans under a profit-sharing system based on Islamic principles. The historical development of BMT in Indonesia originated from grassroots initiatives that applied various sharia contracts in Islamic muamalah. In the context of microfinance, BMT’s contributions to community economic empowerment—such as business financing, training and mentoring, local economic development, social fund management (ZISWAF), income generation, and poverty alleviation—have effectively enhanced financial inclusion by providing access to financial services for individuals and community groups previously underserved by conventional financial institutions